Efficacy of water-based propolis in preventing intra-abdominal adhesions in an experimental rat model - Polat, Eren; Sakin, Dilan Selin; Cimen, Irmak; Kaya, Emre; Can, Batuhan; Ozoner, Ozgur; Pekince-Ozoner, Merve (Univ Zulia, Facultad Ciencias Veterinarias, 2026)
Intra-abdominal adhesions are one of the most common postoperative complications following surgical procedures. Globally, it is among the leading causes of hospital readmissions, chronic pain, and serious conditions such as infertility in both human and veterinary medicine. The risk of development is particularly high after pelvic and abdominal surgeries. Despite this common condition, there is still no effective and reliable treatment method to prevent adhesions. This study aims to evaluate the potential effect of propolis (both oral and intra-abdominal) with its anti-inflammatory and antioxidant properties in the prevention of intra-abdominal adhesions. The rats used in the study were divided into five: Healthy Control Group , Control Group , Sham Group , Oral Propolis Group , and Intra-abdominal Propolis Group . After the intra-abdominal adhesion model was established in rats, excluding the Healthy Control Group and Sham Group, rats in the Oral Propolis Group were administered 75 mgkg-1 of propolis orally once daily for 20 days, while rats in the Intra-abdominal Propolis Group received a single dose of 75 mgkg-1 of propolis intra-abdominally. Results showed that the Oral Propolis Group and Intra-abdominal Propolis Group were statistically significantly lower than the Control Group in terms of macroscopic adhesion scores. Although there was no statistically significant difference when the Oral Propolis Group and Intra-abdominal Propolis Group were compared with the Control Group in terms of fibrosis, it was observed that the Intra-abdominal Propolis Group was statistically significantly lower than the Control Group in terms of inflammation severity. Biochemical analyses, it was revealed that the oxidative stress parameters of rats in both oral and intra-abdominal propolis application were statistically different from the Control Group and that these two were close to the Healthy Control Group in terms of oxidative stress. As a result, it was concluded that both intra-abdominal and oral propolis applications prevent the formation of intra-abdominal adhesions and can be used for prophylactic purposes after abdominal and pelvic operations.
El uso eficaz del propóleo hidrosoluble en la prevención de adherencias intraabdominales en un modelo experimental de ratas
Keywords: Propolis; intra-abdominal adhesion; fibrin; rat